Partial Purification and Characterization of Glutathione S-Transferases from Kedah-Kelantan Cattle (Bos Indicus) and Water Buffalo (Bubalus Bubalis) Liver - Saleh Huddin, Lailatul Jumaiyah (2006)
Biotransformation and detoxification process in living organisms consists of two phases, phase I and phase 11. Phase I involves in the introduction of functional group into molecule while the phase I1 involves the conjugation of phase I metabolites. In phase 11, glutathione S-transferases (GSTs; EC 2.5.1.18) has aroused much interest because of its involvement in the biotransformation and detoxification of wide spectrum of xenobiotics which can be from pesticides, herbicides and insecticides. The present study was undertaken to puriG and characterized cytosolic GSTs from livers of Kedah-Kelantan cattle (Bos indicus) and Malaysia water buffalo (Bubalus bubalis). The glutathione Stransferases were isolated from two important livestock livers, Kedah-Kelantan cattle (Bos indicus) and Malaysian water buffalo (Bubalus bubalis) by glutathione affinity chromatography. The affinity-glutathione chromatography successfully purifies the GSTs isoenzymes with 14.73% yield (62.77 purification fold) and 19.71 % yield (20.44 purification fold) for KK cattle and water buffalo livers respectively. Initial methods of purification included centrifugation and ultracentrifugation. The affinity elution with highest activity towards CDNB was estimated for the pI values using isoelectric focusing method via LKB-8 100 ampholyte type (LKB Bromna) apparatus. pI values for affinity purified KK cattle liver are 5.7 (C-34), 6.9 (C-38) and 8.8 (C-42). While for the water buffalo liver, the pI values for glutathione affinity purified isoenzymes are 6.85 (B-23) and 7.2 (B-24). The isoenzymes were then tested using SDS-PAGE method for purity and also to estimate the molecular weight estimation. It has been estimated that molecular weight for water buffalo isoenzymes of B-23 was 29.3 * 0.05 kDa and B-24 was 30.74 * 0.16 kDa. The KK cattle liver isoenzymes molecular weight was estimated with C-34 was 29.9 * 0.14; C-38 was 28.3 * 0.09 and 27.7 *0.03 for C-42. The study showed that KK cattle liver GSTs exist as isoenzymes (PI 8.8, 6.9 and 5.7), and have high activity towards CDNB, low towards DCNB and no activity towards the ethacrynic acid for the substrate specificities. On the other hand, the water buffalo liver GSTs exist as isoenzymes with pI 6.85 and 7.2. For the substrate specificities, the isoenzymes also have high activity for CDNB, but low for DCNB and could not be detected for the ethacrynic acid.